A Study of Software Reliability Growth with Imperfect Debugging for Time-Dependent Potential Errors - Chiu, Kuei-Chen; Huang, Yeu-Shiang; Huang, I-Chi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Over the last few decades, various software reliability growth models (SRGM) have been proposed, and in recent years a gradual but marked shift has been focused on the balance between acceptable software reliability and affordable software testing cost. Chiu et al.(2008) proposed an SRGM from the perspective of learning effects which is more flexible in fitting various software error data, although it has a restrictive assumption of constant number of potential errors. In this paper, we consider a software reliability growth model in which the number of potential errors varies over the debugging period, since wrongly fixing an error may cause more errors; while correctly debugging one error may resolve others. However, such variation would gradually converge as the testing staff becomes more familiar with the software system. In order to describe this phenomenon, a sine function is introduced in this study to describe the time-dependent behavior of the number of potential errors with imperfect debugging, and the expected testing cost is thus evaluated to assist in the determination of an optimal software release policy. A numerical example is illustrated to verify the effectiveness of the proposed approach.